2019
DOI: 10.1093/mnras/stz1318
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter stripping in galaxy clusters: a look at the stellar-to-halo mass relation in the Illustris simulation

Abstract: Satellite galaxies in galaxy clusters represent a significant fraction of the global galaxy population. Because of the unusual dense environment of clusters, their evolution is driven by different mechanisms than the ones affecting field or central galaxies. Understanding the different interactions they are subject to, and how they are influenced by them, is therefore an important step towards explaining the global picture of galaxy evolution. In this paper, we use the publicly-available high resolution hydrod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 101 publications
(142 reference statements)
6
25
0
1
Order By: Relevance
“…A further formation channel is DM stripping of satellite galaxies, particularly in extreme environments such as clusters (Ogiya 2018;Jing et al 2019;Niemiec et al 2019). Indeed, both N-body simulations in a range of environments, from Milky-Way mass halos (Hayashi et al 2003;Kravtsov et al 2004;Diemand et al 2007;Rhee et al 2017;Buck et al 2019) to clusters (Ghigna et al 1998;Gao et al 2004;Tormen et al 2004;Nagai & Kravtsov 2005;van den Bosch et al 2005;Giocoli et al 2008;Xie & Gao 2015), and analytical models (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further formation channel is DM stripping of satellite galaxies, particularly in extreme environments such as clusters (Ogiya 2018;Jing et al 2019;Niemiec et al 2019). Indeed, both N-body simulations in a range of environments, from Milky-Way mass halos (Hayashi et al 2003;Kravtsov et al 2004;Diemand et al 2007;Rhee et al 2017;Buck et al 2019) to clusters (Ghigna et al 1998;Gao et al 2004;Tormen et al 2004;Nagai & Kravtsov 2005;van den Bosch et al 2005;Giocoli et al 2008;Xie & Gao 2015), and analytical models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mamon 2000;Gan et al 2010;Han et al 2016;Hiroshima et al 2018) have shown that DM stripping is ca-pable of removing parts of a galaxy's halo in group and cluster environments. It has been suggested that this process could drive a large scatter in the stellar-to-halo mass relation for satellite galaxies in groups and clusters, moving them from their initial positions towards lower halo masses (Vale & Ostriker 2004;Smith et al 2016;Bahé et al 2017;Rhee et al 2017;Niemiec et al 2017Niemiec et al , 2019, and therefore lower M halo /M ★ values.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (e.g. Behroozi et al 2014;Niemiec et al 2019) found that infalling dark matter haloes start losing their dark matter around similar cluster-centric distances, i.e. ∼1.5-1.8R 200 .…”
Section: How Gas-loss Since Infall Relates To Cluster-centric Distancementioning
confidence: 85%
“…Extending HST observations to ∼3/4 R vir also provides stringent observational constraints for the study of galaxy evolution within dense environments. Niemiec et al (2019) studied and quantified dark matter stripping of galaxy halos during their infall into clusters, as well as the evolution of their stellar mass and star formation using the Illustris-1 simulation. Such studies are often made in aggregate on a large number of clusters, but BUFFALO will do it on a cluster-by-cluster basis, avoiding smoothing out smallerscale influences on individual clusters.…”
Section: Structure Evolution and Dark Matter Physicsmentioning
confidence: 99%